To solve the equation, we can follow these steps:
1. Distribute the 6 to both terms inside the parentheses:
6(x-1) - 4x + 11 = x - 1 + x
6x - 6 - 4x + 11 = x - 1 + x
2. Combine like terms on both sides of the equation:
(6x - 4x) + (11 - 6) = 2x - 1 + x
2x + 5 = 3x - 1
3. Move all terms involving x to one side of the equation:
2x - 3x + 5 = -1
4. Combine like terms on the left side of the equation:
-x + 5 = -1
5. Move the constant term to the right side of the equation:
-x = -1 - 5
-x = -6
6. Multiply both sides of the equation by -1 to solve for x:
x = 6
Therefore, the solution to the equation 6(x-1)-4x+11=x-1+x is x = 6.
6(x-1)-4x+11=x-1+x
1 answer